An Introduction to Global Financial Markets / An Extensively Revised Edition of an Introduction to Western Financial Markets - Valdez Stephen; Macmillan Business (2000)
This book provides a broad and balanced introduction to the principal global financial markets and institutions from the key global centres - US, Japan, UK, Germany and France. Preface, Acknowledgements, Introduction, The Debt Merry-Go-Round, Banking, Banking Background, The Role of the Central Bank, Commercial Banking, Investment Banking, Securities Markets, The Money and Bond Markets, Stock Exchanges, Foreign Exchange and International Trade, Foreign Exchange, Trade Finance, European Economic and Monetary Union, Derrivative Products, Traded Options, Financial Futures, Other Derivative Products, Insurance, The Periodic Global Crises, Global Financial Crises, Trends in the Global Financial Markets, Glossary, Index.